What is the appropriate management of a trauma‐associated upper extremity deep vein thrombosis (DVT)?. Issue 9 (September 2015) - Beckwith, Jennifer A.; Roy, Elora
Abstract : Evidence‐based answer: The answer is not completely clear. For patients with catheter‐associated upper extremity DVT, removal of the catheter results in faster improvement. Anticoagulation treatment does not appear to provide faster resolution compared with no treatment in the short term (SOR: C, small cohort trials). Still, treatment with parenteral heparin followed by long‐term anticoagulation is recommended (SOR: C, expert opinion).